2022
DOI: 10.3389/fmicb.2022.1053153
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of abamectin on soil microbial communities in the short term

Abstract: With the widespread use of abamectin in agriculture, there is increasing urgency to assess the effects of abamectin on soil microorganisms. Here, we treated plant–soil microcosms with abamectin at concentrations of 0.1 and 1.0 mg/kg and quantified the impacts of abamectin on bulk and rhizosphere soil microbial communities by shotgun metagenomics after 7 and 21 days of exposure. Although abamectin was reported to be easily degradable, it altered the composition of the soil microbial communities, disrupted micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The two most abundant phyla in the vegetable roots were Proteobacteria and Actinobacteria , which can promote plant growth and produce secondary metabolites with antimicrobial properties [ 56 ]. The dominant bacterial phyla in vegetable roots were observed to be significantly grown in experiments involving veterinary antibiotics exposure, which are known to contain bacteria with tolerance and degradation capabilities [ 16 , 17 , 18 ]. In addition, Bacteroidetes were abundant in the vegetable roots, which facilitates the degradation of macromolecules, such as starch, cellulose, or proteins [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two most abundant phyla in the vegetable roots were Proteobacteria and Actinobacteria , which can promote plant growth and produce secondary metabolites with antimicrobial properties [ 56 ]. The dominant bacterial phyla in vegetable roots were observed to be significantly grown in experiments involving veterinary antibiotics exposure, which are known to contain bacteria with tolerance and degradation capabilities [ 16 , 17 , 18 ]. In addition, Bacteroidetes were abundant in the vegetable roots, which facilitates the degradation of macromolecules, such as starch, cellulose, or proteins [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory experiments have shown that the antibiotic activity of a microbial community is influenced by the concentration, exposure time, and type of antibiotic [ 15 ]. Antibiotic effects can be attributed to single species such as Aeromonashydrophila , Aeromonassalmonicida , and Ediwardsiellatarda , as well as larger microbial communities such as fungi and bacteria [ 15 , 16 ]. Observations have shown that the percentages of some classes, including Bacilli , Bacteroidia and Gammaproteobacteria , have significantly grown in experiments involving veterinary antibiotics exposure, which are known to contain bacteria with tolerance and degradation capabilities [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained are in line with those presented in the scientific literature. Indeed, antibiotics caused alterations in endospheric bacterial communities' structures [32,62,64], and those alterations were more pronounced in the root endosphere compared with the leaf endosphere [65,66].…”
Section: Bacterial Community Analysis Endospheric Bacterial Communiti...mentioning
confidence: 99%
“…It is also known to have low toxicity towards avian species and humans [37,38]. However, certain studies show that it is classified as a highly toxic pesticide for mice and rats and has negative effects on soil microbial communities in the short term [39]. To preserve the ecofriendliness of these push-pull strategies, a low concentration of abamectin was used in all the experiments.…”
Section: Introductionmentioning
confidence: 99%